Acrylamide/2-Acrylamido-2-methylpropanesulfonic acid/1-Vinyl-2-pyrrolidinone Terpolymeric Microspheres by Orthogonal Experiments - Zhao, Qian; Lin, Meiqin; Dang, Shuangmin; Hua, Zhao (Asian Journal of Chemistry, 2014)
Polyacrylamide microspheres were soft, flexible, deformable, thermostability and halotolerant micro-gel particles that could be used as deep profile control agent in oil fields with the ultimate purpose of improving oil recovery. In this study, a series of terpolymeric microspheres were prepared through inverse suspension polymerization using the monomers of acrylamide (AM), 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and 1-vinyl-2-pyrrolidinone (NVP). By orthogonal experiments, the formulation optimized can be selected. The shape and size were investigated by electron microscope (EMS), scanning electron microscope (SEM) and light diffraction particle size analyzer and the thermal stability was examined by high-temperature water solution. The experimental results showed that the terpolymeric microspheres has good monodispersity. Under suitable reaction conditions, the particle size and swelling properties of microspheres were influenced significantly by the monomer ratio.